Agroecological evaluation of profiles with eroded arable and virgin soil in the pot experiment with pea at the northern part of steppe zone of Ukraine - Kharytonov, Mykola; Харитонов, Микола Миколайович; Pashova, Valentina; Пашова, Валентина Трифонівна; Bagorka, Mariia; Багорка, Марія Олександрівна; Mytsyk, Oleksandr; Мицик, Олександр Олександрович; Tkalich, Yuriy; Ткаліч, Юрій Ігорович; Lemishko, Svitlana; Лемішко, Світлана Миколаївна (Nicolaus Copernicus University, 2025)
The effective fertility of the humus horizon of mildly washed soil in terms of the productivity of aboveground mass of peas is the highest among all humus genetic horizons. The fertility of the upper horizon with very prominent humus accumulation (Hp), lower transition horizon, with little humus (Phc), and underlying parent material (Pc) horizons is 20% lower than the upper horizon with very prominent humus accumulation (H) horizon. The accumulation of macroelements by peas on the soils of virgin slopes is less than on the soils of arable slopes - by 18% for nitrogen, 36% for phosphorus, and 15% for potassium. The maximum accumulation of nitrogen, phosphorus and potassium by pea was on mildly sloped soil from the 0-10 and 10-20 cm layer comparative to moderately sloped one. The absorption of trace elements by pea depends on environmental conditions and can be divided into three groups: elements of high concentration - Fe, Mn, Zn, medium - Cu, Ni and Pb, and low - Co and Cd. An established pattern: the content of trace elements in plants grown in deeper layers decreases. Ефективна родючість гумусового горизонту слабозмитого ґрунту за продуктивністю надземної маси гороху є найвищою серед усіх гумусових генетичних горизонтів. Родючість верхнього горизонту з дуже помітним накопиченням гумусу (Hp), нижнього перехідного горизонту з невеликим вмістом гумусу (Phc) і підстилаючих горизонтів материнського матеріалу (Pc) на 20% нижча, ніж у верхнього горизонту з дуже помітним горизонтом накопичення гумусу (H). Накопичення макроелементів горохом на ґрунтах цілинних схилів менше, ніж на ґрунтах орних схилів – на 18 % азоту, 36 % фосфору, 15 % калію. Максимальне накопичення азоту, фосфору і калію горохом спостерігалося на помірно нахиленому ґрунті з шару 0-10 і 10-20 см порівняно з помірно нахиленим. Поглинання мікроелементів горохом залежить від умов навколишнього середовища і може бути розділене на три групи: елементи високої концентрації - Fe, Mn, Zn, середньої - Cu, Ni і Pb і низької - Co і Cd. Встановлена закономірність: у рослинах, вирощених у глибших шарах, знижується вміст мікроелементів.
Агроекологічна оцінка профілів еродованого орного та цілинного ґрунту в горщиковому досліді з горохом у північній частині степової зони України
Keywords: soil profile; ґрунтовий профіль; pea; горох; productivity; продуктивність; element accumulation; накопичення елементів